SYSTEM OF EDUCATIONAL SCIENCES: EXPIRIENCE OF EUROPEAN UNIVERSITIES - Bulvinska, Oksana (Continuing Professional Education: Theory and Practice, 2020)
The article is devoted to the system of science of education in the European Universities. For analyzes were provided 16 European Universities from Finland, Belgium, Netherlands, Norway, which are in top 50 in QA World Rankings 2019, and also Humboldt-Universitat zu Berlin and Alma Mater Studiorum – University of Bologna. The main study is the analysis of the study programs about the education in the universities that are listed above. The conclusion, that in most European Universities offered educational programs «Educational studies», which are mainly not for professional, but academic level (especially the Master’s degree). The programs «Educational studies» focused on the study of educational systems and the practical studying in a wide social, cultural, political and economic areas. As usual, this educational program combines the ideas and the study of the educational systems, psychology, sociology, philosophy, history, politics, the management of education, history and culture of education, comparative educational studies, and also the critical analysis of different educational theories and innovative methods. The pedagogical science is one of the educational discipline, which is focused only on the pedagogical problems, which are learning, teaching and development: the educational programs, the measurement and evaluation in education and training, the special pedagogic, which is focused on prevention, research, diagnosis, development and education of children, teenagers or adults with behavioral and emotional problems and their psychosocial consequences. The pedagogical study programs also are focused on development and education of the kids and teenagers in a different social groups (families, schools, groups of friends etc.).